2012
DOI: 10.2217/fca.12.31
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Warfarin Pharmacogenetics in under-represented Minority Groups

Abstract: Genotype-based dosing recommendations are provided in the US FDA-approved warfarin labeling. However, data that informed these recommendations were from predominately Caucasian populations. Studies show that variants contributing to warfarin dose requirements in Caucasians provide similar contributions to dose requirements in US Hispanics, but significantly lesser contributions in African–Americans. Further data demonstrate that variants occurring commonly in individuals of African ancestry, but rarely in othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 81 publications
3
62
0
1
Order By: Relevance
“…1A). The presence of a potential novel haplotype may support the notion that the most common haplotypes defined by Rieder do not completely capture all VKORC1 haplotypes, but rather a range of them (99-62%) depending on the ethnic group investigated (Cavallari and Perera, 2012).…”
Section: Extensive Metabolizersmentioning
confidence: 80%
See 1 more Smart Citation
“…1A). The presence of a potential novel haplotype may support the notion that the most common haplotypes defined by Rieder do not completely capture all VKORC1 haplotypes, but rather a range of them (99-62%) depending on the ethnic group investigated (Cavallari and Perera, 2012).…”
Section: Extensive Metabolizersmentioning
confidence: 80%
“…Current knowledge on genes and genotypes that affect drug safety and efficacy have been mostly reported on Caucasian populations hence, the use of validated variants to tailor drug use cannot be freely extrapolated to other countries (Daar and Singer, 2005;Flockhart et al, 2009). Moreover, it is well recognized that native, Mestizos, or Hispanics in America are underrepresented in pharmacogenetic studies even more evidently than African Americans (Cavallari and P. MA, 2013). And although endeavors are currently ongoing, a complete characterization of the genetic diversity among diverse ethnic groups still encompasses a titanic task (Reich et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who metabolize warfarin slowly can build up dangerously high levels of warfarin if dosing is not carefully adjusted [31,32]. Commonly tested variants in CYP2C9 and VKORC1 are more prevalent in European Americans than in African Americans, while some variants are either more or less prevalent in Chinese individuals [33,34,35,36,37,38]. Furthermore, it has been shown that some variants are better at predicting dosage compared to other variants [32].…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Additional optional reading on warfarin pharmacogenetic dosing algorithms and genotypeguided warfarin dosing in minority populations was recommended. 7,8,26 The student, resident, or fellow and the faculty member spent time discussing the readings prior to applying them to patient care or research. Further, because most of the patients at the medical center were of minority descent, the faculty member devoted significant time to discussing the effect of ancestry on warfarin genetics, emphasizing the concepts of allele and genotype frequencies, haplotypes, and linkage disequilibrium.…”
Section: Training Opportunities For Students and Residentsmentioning
confidence: 99%
“…24,25 Additional optional reading on warfarin pharmacogenetic dosing algorithms and genotypeguided warfarin dosing in minority populations was recommended. 7,8,26 The student, resident, or fellow and American Journal of Pharmaceutical Education 2013; 77 (8) Article 175.…”
mentioning
confidence: 99%